Il ruolo dei marchi di qualità dell’Unione Europea nelle strategie competitive delle piccole e medie imprese agroalimentari italiane - Antonelli, Gervasio; Vigano, Elena (Piccola Impresa / Small Business, 2012)
This paper analyses from both theoretical and operative points of view the issues concerning small and medium-sized italian agrifood enterprises pursuing strategies aimed at differentiating their supply on market by using the marks of the EU on Protected designation of origin (Pdo and Pgi). After having illustrated the quality policy of the European Union and highlighted the potential and constraints resulting from the EU regulation of Pdo/Pgi system on enterprises strategies, the paper analyses some of the main features of the production sector operating within such a system. Subsequently, the paper analyses the most suitable organizational framework to implement market management approaches in order to allow enterprises to achieve a competitive advantage through a product differentiation strategy. Finally, strategic options to this purpose